Information and communication technology (ICT) and economic growth in Iran: causality analysis - Mohammad Haghshenas,; Hasmiah Kasimin,; Madeline Berma, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Iran is currently implementing policy measures to increase the contribution of Information and Communication Technology (ICT) to economic performance. However, little attention is given to examining whether ICT investment contributes to the economic growth of Iran. Concerning the importance of the causal link between these two variables to national policy implications, the present study employs a Granger causality analysis to examine the cause and effect relationship between ICT infrastructure and output growth in a multivariate setting that includes labor and capital variables. The results indicate that a long-run equilibrium relationship exists between ICT development and economic growth. Furthermore, the findings provide evidence of significant uni-directional short-run causality running from economic growth to ICT development in the Iranian economy. In terms of policy implications, the findings support the idea that this relationship is sustainable. However, in the short-run, investing in other important sectors and promoting ICT-use should be a priority for boosting the development of the national economy and ICT.